Frequency spectral analysis of electrical partial discharge signals in XLPE cable under various soil conditions - Md Thayoob Y.H.; Ghosh P.S.; Ghani A.B.A. (2023)
As XLPE cables age, partial discharge (PD) testing on the cables has gained a lot of attention in the power utilities. This is because PD has been found to be a good indicator of the insulation health. In this research work, an experiment has been carried out in order to acquire electrical PD signals from an 11KV, single-core 240mm2 XLPE cable. The operating conditions are varied using two parameters which are the soil thermal resistivity and cable loading in terms of core temperature. The analysis of PD signals has been commonly carried out in the time domain. However, in this paper, the analysis of PD signal patterns in an XLPE cable due to various soil conditions is performed in the frequency domain. As such, the timedomain electrical PD signals from the PD measurement system are first transformed into frequency spectrum using fast Fourier transform (FFT). Then, the variations in the spectral content due to the changes in the soil condition at a fixed temperature of the cable are analyzed. From the results obtained, it is clearly evident that the changes in the soil thermal resistivity have significant effect on the spectral content of the PD signals. 2008 IEEE.